Konsentrasi Timbal (Pb) pada Daging Udang Hasil Tangkapan Nelayan di Desa Jungkat Kecamatan Siantan Kabupaten Mempawah - Diah Wulandari Rousdy, Dwi Ayu Lestari, Junardi (Jurnal Protobiont, 2018)
Prawn are being polluted by lead from transportation, industrial and others activity around of Kapuas River. The purpose of this research was find out concentration of lead (Pb) in various prawn’s flesh. Sample of prawns were collected using purposive sampling. Concentration lead was measured by using Atomic Absorption Spectrophotometry method at Directorate Research and Industrial Standardization West Borneo. Data were subjected on ANOVA and correlation test. This research was used Endeavouri prawn (Metapenaeus ensis), Tiger Cat Shrimp (Parapenaeopsis sculptilis) and White Prawn (Penaeus merguiensis). Concentration of lead in prawn’s flesh were collected on April and May were <0.04 mg/kg. Concentration of lead that analyzed on June in P. merguiensis was lowest (0.065 mg/kg) and the highest was in M. ensis (0.073 mg/kg). There was no differences of lead concentration in various species were collected on common month. The differences of lead concentration were significant found in common species were collected on various month. The concentration of lead were below by allowed quality standard for prawn which is 0.5 mg/kg. There was no correlation between number of sample, body length and rainfall to concentration of lead in prawn’s flesh. The was correlation between number of rainy day and ship to concentration of lead in prawn’s flesh.